Holistic Framework for the Implementation and Validation of PBF-LB/M with Risk Management for Individual Products through Predictive Process Stability - Groneberg, Hajo; Oberdiek, Sven; Schulz, Carolin; Hofmann, Andreas; Schloske, Alexander; Doepper, Frank (Journal of Manufacturing and Materials Processing, 2024)
The additive manufacturing technology powder bed fusion of metal with a laser beam (PBF-LB/M) is industrially established for tool-free production of complex and individualized components and products. While the in-processing is based on a layer-by-layer build-up of material, both upstream and downstream process steps (pre-processing and post-processing) are necessary for demand-oriented production. However, there are increasing concerns in the industry about the efficient and economical implementation and validation of the PBF-LB/M. Individual products for mass personalization pose a particular challenge, as they are subject to sophisticated risk management, especially in highly regulated sectors such as medical technology. Additive manufacturing using PBF-LB/M is a suitable technology but a complex one to master in this environment. A structured system for holistic decision-making concerning technical and economic feasibility, as well as quality and risk-oriented process management, is currently not available. In the context of this research, a framework is proposed that demonstrates the essential steps for the systematic implementation and validation of PBF-LB/M in two structured phases. The intention is to make process-related key performance indicators such as part accuracy, surface finish, mechanical properties, and production efficiency controllable and ensure reliable product manufacturing. The framework is then visualized and evaluated using a practice-oriented case study environment.